2011
DOI: 10.1071/ch11177
|View full text |Cite
|
Sign up to set email alerts
|

Ion Translocation in Artificial Molecule-based Systems Induced by Light, Electrons, or Chemicals

Abstract: Synthetic molecules and nanodevices, like their more elaborate biological counterparts, have been shown to perform several sophisticated functions, using even fairly simple molecular architectures. One limitation to developing artificial molecular arrays and networks from these miniscule building blocks is the lack of a unifying strategy whereby they can communicate or interact together, which has been successfully developed in natural systems. Understanding and harnessing these efficient biological processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…On the other hand, while a wealth of photoionic systems is known, artificial molecular systems utilizing chemical transfer between functional molecules are scarce and typically rely on transfer of metal ions or protons . Concerning the latter, photoactive variants have been reported using spiropyran chromophores for reversible ion binding . Utilization of molecules, rather than ions, as messengers in such a scheme has not been duly considered.…”
mentioning
confidence: 99%
“…On the other hand, while a wealth of photoionic systems is known, artificial molecular systems utilizing chemical transfer between functional molecules are scarce and typically rely on transfer of metal ions or protons . Concerning the latter, photoactive variants have been reported using spiropyran chromophores for reversible ion binding . Utilization of molecules, rather than ions, as messengers in such a scheme has not been duly considered.…”
mentioning
confidence: 99%
“…could form the basis of a bistable molecular switch. [19][20][21]27 Therefore, the possibility of reversing the translocation of palladium that occurs in the transformation of 3b to 5 was explored. A range of different conditions including heating at high temperatures in a range of solvents, and treatment with bases or acids were investigated, but no conditions were found that would return 3b or 3a from 5.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Metal derivatives of macrocycles with these features have been investigated as receptors for anions and small molecules, [3][4][5][6][7][8] for the binding and activation of molecules during metal catalysed transformations, [9][10][11][12] for the formation of rotaxanes, catenanes, and molecular devices, [13][14][15][16][17][18] and as the basis of molecular switches through the controlled translocation of metal ions between coordination pockets within the macrocyclic ligand. [19][20][21] In this paper we describe (i) the synthesis of the 22 ring atom macrocyclic ligand H 4 L (Scheme 1) which has two potential coordination pockets, (ii) the selective coordination of Pd(II) to the "tail" coordination pocket of the macrocycle to give the compounds [PdX(H 3 L)] (3a, X = Cl; 3b, X = OAc) (Scheme 2), (iii) conditions under which the Pd(II) ion in 3b undergoes translocation to the "head" coordination pocket to give [Pd(NH 2 R)(H 2 L)] (4, R = n-Bu; 5, R = N-(3-aminopropyl)caprolactam), (iv) the direct synthesis of the compounds [Pd(OH 2 )(H 2 L)] (6) or 5, where palladium is coordinated in the "head" pocket, (v) formation of the complexes [Pd(DBU)(H 2 L)] (7), 4 or 5 through simple displacement of the labile aqua ligand in 6, (vi) the evidence that hydrolysis of DBU to produce the N-(3-aminopropyl)caprolactam ligand in 5 is catalysed by the acetic acid formed during ligand metallation rather than by coordination to palladium, and (vii) the X-ray crystal structure determinations of H 4 L, 3a, 5, and 6.…”
Section: Introductionmentioning
confidence: 99%
“…Metal cations are an interesting alternative to protonsw hen designing chemical communication in molecular and supramolecular systems. [33] Thiss tatementi si np art motivated by the rich redox chemistryo fm etal cations, allowing for the use of electron transfer (involving chemical speciesorelectrochemistry) as the externalt rigger mechanism. The group of van der Boom reported in 2008 surface-immobilized monolayers of Ru 2 + -a nd Os 2 + -polypyridyl complexes and their use for logic operations.…”
Section: Chemical Communication Through Release Of Metal Cationsmentioning
confidence: 99%
“…Metal cations are an interesting alternative to protons when designing chemical communication in molecular and supramolecular systems . This statement is in part motivated by the rich redox chemistry of metal cations, allowing for the use of electron transfer (involving chemical species or electrochemistry) as the external trigger mechanism.…”
Section: Chemical Communication Through Release Of Metal Cationsmentioning
confidence: 99%